Computer simulation of the density of the state of the NaF nanocrystal - Myasnikova, L.N.; Istlyaup, A.S.; Sergeyev, D.M. (Recent Contributions to Physics, 2019)
At present, various theoretical research methods are intensively used to interpret experimental results related to the study of the properties of defects in solids. Progress in this direction is possible thanks to the improvement of computer technology and the development of modern quantum chemical packages. The paper presents the results of computer simulation of the density of states and the total energy of an ideal NaF nanocrystal (Na13F14, Na4F5, Na22F23) and with the simplest point defects in various cluster compounds (Na12F13, Na21F22). Simulation of characteristics is implemented in the Atomistix ToolKit with Virtual NanoLab program in GGA (generalized gradient approximation) functionality. Objects studied are quantum dots. The results obtained may be useful in the study of nanocrystals.
Keywords: NaF nanocrystal; density of states; band structure; total energy; computer simulation